2021
DOI: 10.1186/s40545-021-00361-4
|View full text |Cite
|
Sign up to set email alerts
|

Access, use and disposal of antimicrobials among humans and animals in Wakiso district, Uganda: a qualitative study

Abstract: Background Inappropriate use of antimicrobials in both humans and animals is a key driver of antimicrobial resistance (AMR). In addition, human behaviours such as poor disposal of antimicrobials in the environment can increase their exposure to microbes which can impact on humans and animals. However, evidence on access, use and disposal of antimicrobials for humans and animals at community level in Uganda is limited. This study therefore explored access, use and disposal of antimicrobials amon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 39 publications
2
18
0
Order By: Relevance
“…Unfortunately, many poultry microorganisms have developed resistance to these antibiotics [ 3 , 45 , 48 ]. Similar information has been reported among African countries [ 3 , 29 , 48 , 49 , 50 ] and this generally calls for more prudent use of antibiotics.…”
Section: Introductionsupporting
confidence: 77%
“…Unfortunately, many poultry microorganisms have developed resistance to these antibiotics [ 3 , 45 , 48 ]. Similar information has been reported among African countries [ 3 , 29 , 48 , 49 , 50 ] and this generally calls for more prudent use of antibiotics.…”
Section: Introductionsupporting
confidence: 77%
“…Other studies have reported similar findings. 40 , 41 This phenomenon is worrying because of the increasing global trends of cross-over use of human and livestock antibiotics often obtained from hospitals and community pharmacies. 7 , 42 …”
Section: Discussionmentioning
confidence: 99%
“…32,33 Furthermore, sharing of prescribed antibiotics amongst household members is common, as is the unauthorized practice of using antibiotics for animal treatment and growth promotion. 34,35 Studies of antimicrobial drug quality in Uganda have largely focused on antimalarials, reporting a high burden of poor-quality and nonquality-assured antimalarials. 36,37 Meanwhile inappropriate pharmaceutical waste disposal and environmental contamination are emerging as neglected risks to sustainable medicines use in Uganda.…”
Section: Gaps In Sustainable Medicines Usementioning
confidence: 99%
“…Active pharmaceutical ingredients have been found in both surface waters and waste treatment facilities 38 . Households in Uganda dispose of unused medications into general waste dumpsters and rubbish pits, 34 contributing to environmental pollution.…”
Section: Gaps In Sustainable Medicines Usementioning
confidence: 99%
See 1 more Smart Citation